Improvement on the quality of life in patients who underwent bariatric surgery - Glauco Barnez Pignata Cattai; Luzia Jaeger Hintze; Alexandre dos Santos Cremon; Cheila Aparecida Bevilaqua; Nelson Nardo Junior; Sonia Silva Marcon (Universidade Estadual de Maringá, 2014)
The objective of this study is to compare the scores of health related quality of life (HRQOL) of candidates for bariatric surgery with patients that underwent bariatric surgery at different time intervals. A cross sectional study was performed in the city of Maringá and Paranavaí, Paraná, Brazil, with 44 candidates to bariatric surgery and 63 individuals submitted to it. The group of individuals submitted to bariatric surgery was divided into 3 subgroups according to the elapsed time of surgery. (more than 18 months - G2; at least 19 and maximum 36 months - G3 and more than 36 months - G4).The quality of life related to the health of the patients was assessed by the SF-36 and BAROS. The comparison among groups was performed by using parametric and non-parametric statistic tests. The magnitude of the effects of the bariatric surgery by effect size (ES) was also evaluated. The assessment of HRQOL shows differences among the groups, with lower scores observed in group 4 when compared to group2. Acomparison of mean scores of the domains of the SF-36 shows that the groups formed by people who underwent bariatric surgery have average scores significantly higher than those presented by candidates to bariatric surgery (p < 0.05). Though not return to the levels of candidates to bariatric surgery, the scores of the areas "Pain body" and "General health", presented by the groups 2 and 4, as well as those submitted by the groups 2 and 3 for the field "Vitality", suggest a worsening in HRQOL with the passage of time after surgery. The results of this study indicate that people who suffer from morbid obesity have a strong impact on HRQOL and suggest that the implementation of bariatric surgery is able to promote improvements HRQOL important for these people.